New York state, regional and county level nitrogen and phosphorus balances for harvested cropland - Godber, Olivia Florence; Workman, Kirsten; Reed, Kristan; Ketterings, Quirine M. (Frontiers in Sustainability, 2024)
New York (NY) State is one of five states that collectively produce >50% of the annual milk supply within the United States. The local environment allows farmers to integrate crop and livestock systems, facilitating cycling of manure nutrients back to cropland. Thus, dairy provides NY with benefits, opportunities, and challenges in terms of environmental sustainability, climate resiliency, and a circular agricultural economy. Improved balancing of crop nitrogen (N) and phosphorus (P) needs and supply with manure and fertilizer, is key for a circular agricultural economy. The objectives of this study were to calculate and evaluate (1) regional and county level N and P balances of harvested cropland; and (2) contribution of manure to a circular agricultural economy for NY. Nutrient balances were calculated for 2017 (most recent Census year) as the difference in the amount of nutrient input through purchased fertilizer and recoverable manure, and the amount removed in harvested crops. Atmospheric N deposition and legume N fixation, and manure nutrient losses during collection, transfer, storage, and treatment were estimated too. The 2017 P balance was 10 kg P/ha (9 lb P/ac). The N balance was between 39 kg N/ha (35 lb N/ac) and 95 kg N/ha (85 lb N/ac), depending on the proportion of legume cropland assumed to receive manure. Redistribution and application of manure to meet P-removal on non-legume cropland only leaves a surplus of 3 kg P/ha (3 lb P/ac). Applying surplus manure to legume and non-legume cropland results in a slight, statelevel, P deficit. In both scenarios, the large N deficit that cannot be met through legume N fixation alone indicates purchased fertilizer is required. These results show NY's ability to capitalize on the value of manure without excessive risk to the environment. Greater circularity of agricultural production in NY will need to consider benefits and trade-offs of applying manure to legume cropland. As milk production increases in the state, implementation of advanced manure treatment, storage, and manure application and livestock feeding practices will be needed to increase the circularity and sustainability of the agricultural sector in NY.